Removal of a Basic Dye from Aqueous Solution by a Natural Kaolinitic Clay — Adsorption and Kinetic Studies - Jatindra Nath Ganguli; Sangeeta Agarwal (Adsorption Science & Technology)
The < 25 μm fraction of natural clay containing kaolinite, chlorite, illite and illite/smectite mixed layered clay minerals was characterized and used as a potential adsorbent for the removal of Rhodamine B (RB) dye from aqueous solution. Adsorption experiments were carried out in batch mode by varying the following parameters: pH, temperature, initial dye concentration, adsorbent dosage and time of contact. The equilibrium data were well fitted by both the Langmuir and Freundlich adsorption isotherms. The Langmuir monolayer adsorption capacity was found to be 4.77 mg/g, which was better than the value reported for kaolinite (1.95 mg/g). The adsorption process followed pseudo-second-order kinetics. Negative ΔG 0 values indicated that adsorption onto this clay was a spontaneous process. A maximum dye uptake of > 90% was achieved at 313 K employing an initial dye concentration of 4.8 × 10 −6 M, a pH value of 2 and an adsorbent dosage of 1 g/ℓ.